Social value and organizational performance in non-profit social organizations - Felício, J. Augusto (2022)
This paper analyzes the roles of social entrepreneurship and transformational leadership in explaining the social value and the organizational performance of non-profit social organizations. By evaluating the role of socioeconomic context as the moderating variable, the results confirm the strong influence of social entrepreneurship on social value and the effects of social entrepreneurship and transformational leadership on organizational performance. The socioeconomic context proves to be an important moderator of the hypothesized relations. In an unfavorable context, transformational leadership becomes relevant in explaining social value and organizational performance. However, in a favorable context, social entrepreneurship provides more significant support to social value and organizational performance, and social value itself also has an effect on organizational performance.